Effect of salt concentration on dielectric properties of Li-ion conducting blend polymer electrolytes - Arya, Anil; Sharma, A. L. (Journal of materials science. Materials in electronics, 2018)
In the present article, we have studied the effect of the salt concentration (LiPF 6 ) on transport properties and ion dynamics of blend solid polymer electrolyte (PEO–PAN) prepared by solution cast technique. Fourier transform infrared (FTIR) spectroscopy confirms the presence of microscopic interactions such as polymer–ion and ion–ion interaction evidenced by a change in peak area of anion stretching mode. The fraction of free anions and ion pairs obtained from the analysis of FTIR implies that both influence the ionic conductivity with different salt concentration. The complex dielectric permittivity, dielectric loss, complex conductivity have been analyzed and fitted in the entire frequency range (1 Hz–1 MHz) at room temperature. The addition of salt augments the enhancement of dielectric constant and shift of relaxation peak in loss tangent plot toward high frequency indicates a decrease of relaxation time. We have implemented the Sigma representation (σ″ vs. σ′) for solid lithium ion conducting films which provide better insight regarding the dispersion region in Cole–Cole plot (ε″ vs. ε′) in lower frequency window. The dielectric strength, relaxation time and hopping frequency are in correlation with the conductivity which reveals the authenticity of results. Finally, the ion transport mechanism was proposed for getting the better understanding of the ion migration in the polymer matrix.